2020
DOI: 10.1111/jog.14184
|View full text |Cite|
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii and Toxocara spp. infections among pregnant women with and without previous abortions in the west of Iran

Abstract: Aim In spite of the importance of toxoplasmosis and toxocariasis among the high‐risk groups, such as pregnant women, the infections are categorized as a neglected tropical disease by the World Health Organization. Toxoplasma gondii and Toxocara spp. infections can cause systemic and ocular diseases in infants during pregnancy. In this study, we investigated seroprevalence and risk factors of toxoplasmosis, toxocariasis and their co‐infection in pregnant women and non‐pregnant women referred to the healthcare f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
2
9
1
1
Order By: Relevance
“…The funnel graphic utilized for assessment of publication bias showed asymmetry among some studies, probably due to bigger size of effects and lower sample size (Figure 9). Baujat plots showed that three studies (31)(32)(33) add substantially to the heterogeneity in the meta-analysis. However, these studies do not have a large impact on the overall results and were kept in the meta-analysis.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The funnel graphic utilized for assessment of publication bias showed asymmetry among some studies, probably due to bigger size of effects and lower sample size (Figure 9). Baujat plots showed that three studies (31)(32)(33) add substantially to the heterogeneity in the meta-analysis. However, these studies do not have a large impact on the overall results and were kept in the meta-analysis.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…Baujat plots showed that three studies ( 31 33 ) add substantially to the heterogeneity in the meta-analysis. However, these studies do not have a large impact on the overall results and were kept in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human toxoplasmosis occurs mostly via the intake of undercooked or raw meat products infected with tissue cysts [ 8 ], or by ingestion of soil, water, or vegetables infected with sporulated oocysts [ 9 ]. Moreover, T. gondii can be passed through transplacental transmission, blood transfusions, and organ transplantation [ 10 12 ]. T. gondii infection is usually asymptomatic in immunocompetent individuals, but the parasite may induce neurological and ocular disorders in fetuses and immunocompromised patients [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ruminant calves toxocariasis is initiated via trans-placental and transmammary routes and characterized by loss of appetite, weight loss, diarrhea that leads to morbidity and high mortality rate, and results into serious economic losses (Rast et al 2013). Toxocara vitulorum also infects man, likely via cow milk, leading to serious clinical entities, such as visceral and ocular larval migrans, and neurotoxicariasis (Abdel-Rahman and El-Menyawe 2015; Ma et al 2018;Meliou et al 2020;Raissi et al 2020Raissi et al , 2021.…”
Section: Introductionmentioning
confidence: 99%